Acute enteric-coated sodium bicarbonate has negligible effect on anaerobic performance but affects metabolomics and attenuates the gastrointestinal response - Zhou, Nihong; Fan, Yongzhao; Wang, Xiangyu; Wang, Junde; Wu, Hao (Frontiers in Physiology, 2022)
In a randomized crossover design, twelve male college students completed four Wingate anaerobic 30s cycling tests (WACT) after consuming a placebo (PL) and two experimental conditions: 0.2g∙kg–1 body mass in enteric-coated sodium bicarbonate pills (ES) or general sodium bicarbonate pills (GS). Blood lactate (BLA), heart rate (HR), ratings of perceived exertion (RPE), and gastrointestinal–symptoms assessment questionnaire (GSAQ) were measured pre-exercise and post-exercise. In contrast, mean power (MP) and peak power (PP) were recorded immediately post-exercise. Urine samples were collected before formal tests and 50 min after the third WACT. Our findings indicate the following: (1) MP and PP showed no significant difference among conditions . The PP decline of the ES and GS after the 3rd WACT was lower than that of the PL; (2) There were no significant differences in physiological responses, such as BLA, between the three conditions. Although blood lactate concentration after 10 min of the 3rd WACT was lower with ES and GS than with placebo; (3) Fewer participants experienced gastrointestinal symptoms with enteric-coated than with general sodium bicarbonate; (4) The metabolites with differences among the three conditions 50 min after exercise were 3-phospho-D-glycerate, pyruvate, cis-aconitate, oxaloacetate, and citrate. ES had higher levels of 3-phospho-D-glycerate, pyruvate, and cis-aconitate than GS. The 3-phospho-D-glycerate, pyruvate, and cis-aconitate levels in GS were significantly lower than in PL. In contrast, the citrate level in GS was significantly higher than that in other experimental conditions. Compared to PL, the level of oxaloacetate was higher after exercise in ES. These data suggest that supplementation of enteric-coated and general sodium bicarbonate before exercise can alter energy metabolism following anaerobic exercise, involving the metabolism of 3-phospho-D-glycerate, pyruvate, cis-aconitate, oxaloacetate, citrate, and lactate. However, they do not affect anaerobic performance and blood lactate. The supplementation of acute enteric-coated sodium bicarbonate and general sodium bicarbonate can enhance some of the weak effects of blood lactate clearance during anaerobic exercise. In addition, enteric-coated sodium bicarbonate consumption mitigates gastrointestinal symptoms during high-intensity exercise.